Construction of affordable housing using local building materials - Tytok, V. V. (Ways to Improve Construction Efficiency, 2020)
Trends in housing development should be based on the geographical location and climatic conditions of the region, national characteristics and culture, natural resources, transport links, density and living standards. Construction significantly affects the socio-economic development of the region. In this regard, increasing the sustainability of the regional construction complex, which is based on the building materials industry and the construction industry is a relevant and promising area of research. Demand in the building materials market continues to stimulate increased interest in the development of new types of efficient and inexpensive building materials. Since construction is one of the most material-intensive sectors of the economy, which consumes a large number of construction materials and products, various measures are taken to reduce their cost. In this regard, recently in the construction seek to make greater use of local building materials. This allows you to unload transport from long-distance transportation and significantly reduces the cost of construction. However, the building materials industry cannot develop by focusing only on natural sources of raw materials, as the costs of their extraction and processing are constantly growing. The use of man-made waste provides production with a rich source of cheap and often already prepared raw materials, which reduces the cost of manufacturing building materials. One of the promising areas in the construction of affordable housing is the maximum use of building materials and products that can be obtained from local raw materials and industrial waste. As local building materials are offered: clay, sand, soil, straw, reeds, flax. The use of industrial waste solves both environmental, fuel and energy problems and expands the raw material base of building materials.